PERANCANGAM MEDIA PROMOSI PARIWISATA KOTA SOLOK DALAM BENTUK MEDIA CETAK BALIHO - Sheanny Ocmi Sakti; Heldi .; Yahya . (DEKAVE : Jurnal Desain Komunikasi Visual, 2012)
Abstract Design objective is to improve the local investment Solok City, Promoting Solok City as a tourist destination city, As well as providing information and communication to the public in the city and outside the city Solok Solok Billboards using print media, the process of designing a procedural oriented information provision on society. In the design of a media campaign Solok City Tourism is in need of primary data and secondary data and then the data that has been obtained is analyzed using SWOT method. Designing generate major media ie print media and billboard media campaign supporting the main features such as posters, stickers, calendars, pins, shirts, umbrellas, banners, wall clocks and mugs. Kata Kunci: Perancangan Media Promosi Pariwisata kota Solok dalam Bentuk Baliho